Protein Hydrolysate ft’om Miscellaneous Fish - THANKAMMA, R; GOPAKUMAR, K; NAIR, A LEKSHMY; SHENOY, A VASANTH (Fishery Technology, 2017)
A method to prepare fish protein hydrolysate from miscellaneous fish obtained as by catch from shrimp trawlers is outlined. Effect of temperature and concentration of enzyme papain on the yield of hydrolysates has been determined. It is seen that within 30 min at 55Â°C and pH 6.5 fish proteins can be effectively solubilised, provided the nitrogen content of the enzyme (activity 10 units/mg enzyme) and substrate are maintained in the ratio 1 :30. This hydrolysate possesses the best amino acid pattern compared to those obtained after hydrolysis for 60 to 180 min.